Incorporation of Edutainment Into Intervention and Evaluation: The Jump With Jill (JWJ) Program - Jayne, Jill (Frontiers in Public Health, 2019)
Objective: To incorporate media strategies (e.g. edutainment) into a pilot nutrition education intervention, Jump with Jill (JWJ), to (1) change student knowledge and intentions; (2) stimulate enthusiasm; and (3) enhance evaluation. Methods: Third graders (n=193) completed a pre-survey, attended a 60-minute nutrition education show presented as a school assembly, and then completed a post-survey. Data was collected interactively, where students lined up behind an emoji that best represented their answers. Results: Statistically significant improvements were reported for drink preferences and enjoyment of nutrition education as well as the experience of taking a survey. All aggregate responses for knowledge, attitudes and intention became significantly more positive (p=.05). Furthermore, approximately 95% reported positive ratings to participating in the survey (P<0.0001). Discussion: Use of edutainment may serve to stimulate change in nutrition knowledge and intention in 3rd grade students. Perfecting this teaching strategy into evaluations of health promotion programming may serve the field by increasing accuracy of student responses when language, reading level, or survey inexperience are barriers.